Analisis dan Perancangan Sistem Informasi Pemasaran Berbasis Web untuk Komoditi Perkebunan Unggulan pada Dinas Perkebunan Provinsi Jambi - Tampubolon, Musmulyadi; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2018)
The superior estate commodities in Jambi Province are not yet well known in the world market, so a web-based marketing information system is needed to introduce superior estate commodities in Jambi Province. The main problem in the development of information systems is how to analyze and design an information system that suits for use. This study aims to design a web-based marketing information system for superior estate commodities at the Jambi Provincial Estate Service. From the results of the study successfully designed a web-based marketing information system in prototype form. System design uses Use Case Diagrams, Activity Diagrams, and Class Diagrams which can be implemented into web-based marketing information systems for superior estate commodities in Jambi Province